A Study On REITS Market And Its Future Development In Malaysia - Kit, Wong Chun (2009)
The study aims to find out the extent of Malaysia public's understanding of the concept of REITs and its future development in Malaysia. There are lacks of research conducted by researchers to explore more detail in this new investment instrument. There is a great potential to conduct this research as based on the initial survey by the researcher. In this research, the researcher is using the self-administered questionaire to collect the data regarding the public perception on REITs.